Pop-Up Books as a Learning Innovation: Their Influence on Elementary School Students’ Motivation to Learn - Nasution, Mawaddah; Padya, Adiba Dwi; Sitepu, Melyani Sari; Wanda, Karina; Ayu, Lodiana (Attadrib: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
One of the problems that often occurs is that students are lazy to study and like to skip school. In addition, teachers are not successful in providing motivation to students and the minimal use of learning media. One solution that can be used to overcome this problem is to use pop up book media. The purpose of this study was to determine the effect of using pop-up book media on students' learning motivation. The instrument used to measure the effect of motivation was a questionnaire given to students. The population in this study was 42 students. The sampling technique used total sampling, namely all populations were sampled. Data testing was carried out using normality tests, homogeneity tests, N-Gain tests and to answer the hypothesis using the Independent T.Test. The results of the hypothesis show that the value of a < sig is 0.001 < 0.05 which means that pop up book media has an effect on student learning motivation. In addition, the N-Gain acquisition shows that its influence is in the medium category. It can be concluded that Pop UP Book Learning Media has an effect on students' learning motivation in science learning at SDN 067258 Medan Amplas.